Effectiveness of open and close kinetic chains after anterior cruciate ligament reconstruction: A systematic review and meta-analysis - Rizka Salsabila Putri; Suryo Saputra Perdana; Amalia Nur Azizah (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: The Anterior Cruciate Ligament (ACL) is a ligament that has the function to maintain the stability of the knee so that it does not shift excessively towards the front. ACL injuries are injuries that are often experienced by sports athletes, especially those who often make fast and sudden movements. There are non-operative and operative methods for treating ACL. Non-operative methods are considered less effective because they usually require a slightly longer recovery period. One of the most frequently used surgical methods is reconstruction. After reconstruction, there is a need for exercises to speed up recovery and improve its function. Some examples of exercises that can be used are Open Kinetic Chain (OKC) and Close Kinetic Chain (CKC) exercises.Purpose: To determine the level of effectiveness between OKC and CKC for individual after ACL reconstructionMethod: This research was a systematic review and meta-analysis with the PRISMA diagram to filter supporting articles. To assess the quality of Randomized Controlled Trial (RCT) design studies, the Critical Appraisal Checklist was used. Meanwhile, the Characteristics for Included Studies were used to assess the feasibility. The article search came from the Pubmed database with the keywords